Smoking Pack Years and Eustachian Tube Dysfunction - Arjun Sharma; Sam MacDowell; Nihal Punjabi; Sameer Kejriwal; Vikram Sharma; Jared C. Inman (OTO Open, 2024)
Abstract Objective To determine the effect of smoking history on the risk of developing obstructive eustachian tube dysfunction (OETD). Study Design Cross‐sectional review. Setting National database. Methods Data from the National Health and Nutrition Examination Survey (1999 to present) was analyzed. OETD was defined as middle ear pressure less than −100 decapascals (daPa). Nonsmokers, current smokers, with tympanometry data were analyzed. Patients under the age of 18, with myringotomy tubes, or with a sinus problem/earache/cold in the past 24 hours were excluded. The relative risks (RRs) for developing OETD were calculated for nonsmokers versus smokers and those with greater versus less than 10, 20, and 30 pack years (py). Results A total of 9472 patients met inclusion criteria (54.1% female, 75.9% non‐Hispanic, mean age 43, 20.3% smokers). The RR of having OETD for smokers versus nonsmokers was 1.75 [95% confidence interval, CI: 1.45‐2.11]. The RR of having OETD for patients with a 10+ py was 1.97 [95% CI 1.57‐2.47], 20+ py was 2.29 [95% CI 1.76‐2.95], and 30 py or greater was 2.08 [95% CI 1.49‐2.90]. Conclusion In this study, smoking roughly doubled the risk of developing OETD, as represented by a single measurement of negative middle ear pressure less than −100 daPa. The definition of OETD used in this study was limited, as it did not include symptomology, and more work is needed to examine additional covariates. However, these results may guide future research to better counsel and screen patients for OETD.